Correlates of the Militant Extremist Mindset - Furnham, Adrian; Horne, George; Grover, Simmy (Frontiers in Psychology, 2020)
This study aimed to examine bright- and dark-side personality, personal beliefs (religion and politics) and self-evaluation correlates of beliefs in the Militant Extremist Mindset (MEM). In all, 506 young adults completed various self-report measures in addition to the three-dimensional MEM questionnaire. The measures included short measures of the Big Five traits, Self-Monitoring, Self-Evaluation and Personality Disorders, as well as demographic questions of how religious and politically liberal participants were. The Proviolence, Vile World, and Divine power mindsets showed varying correlates, with no consistent trend. Stepwise regressions showed that the demographic, personality and belief factors accounted for between 14% (Vile World) and 54% (Divine Power) of the variance, There were many differences between the results of three mindset factors, but personality disorder scores remained positive predictors of all three. The Vile World mindset was predicted by religiousness, liberalism, personality disorder scores and negative self-monitoring, but not personality traits. Religiousness had a contribution to all subscales and predicted the vast majority of the Divine Power mindset with smaller relationships with personality and personality disorders. Proviolence was predicted by the majority personality measures and sex.